Adaptive Parameter Identification Based Tracking Control of Servo Systems with Unknown Actuator Backlash Compensation - Hailan Du; Liang Tao; Xiongfeng Deng; Binzi Xu (Actuators, 2025)
This paper presents a robust tracking control strategy for servo systems with unknown backlash, employing adaptive parameter identification to address performance degradation caused by backlash nonlinearities. In high-precision positioning and rapid-response applications, backlash significantly compromises system performance. To address this challenge, a servo system model incorporating backlash nonlinearities is developed, and a novel adaptive inverse function is introduced for backlash compensation. The estimation error of unidentified parameters is indirectly obtained through the design of a state observer. Minimizing the estimation error facilitates the accurate identification of model parameters, encompassing those associated with backlash. Additionally, an adaptive law is designed to estimate the unknown upper bounds of disturbance dynamics. Then, a robust tracking controller is proposed, which dynamically adjusts control inputs in real time based on identified backlash parameters to counteract backlash-induced adverse effects. Theoretical analysis and simulation results demonstrate that the proposed strategy significantly improves tracking performance in servo systems with unknown backlash.